PENERAPAN METODE ICONIX PROCESS DALAM PENGEMBANGAN SISTEM INFORMASI KEPEGAWAIAN UNIVERSITAS CATUR INSAN CENDEKIA - Ananda, Fikri; Hatta, Muhammad; Fahrudin, Rifqi; Magdalena, Lena; Asfi, Marsani; Febima, Mesi (Universitas Catur Insan Cendekia (CIC) Cirebon, 2024)
Accurate and precise information plays a crucial role in producing high-quality Human Resources (HR) or employees at Universitas Catur Insan Cendekia. Higher education institutions have various needs in managing HR data, including personal information, educational history, rank classification, and other important employee details. The Iconix Process methodology is employed in the development of the Human Resource System at Universitas Catur Insan Cendekia, starting with requirements analysis, diagram creation, initial design, detailed design, coding, testing, and implementation. The result is a more structured, easily accessible, and efficient management of HR data through a website. Keywords: Iconix Process, Development, Information Systems, Personnel